Characterization of Granulovirus and Nucleopolyhedrovirus Isolated from Spodoptera Litura - Lau, Wei Hong (2002)
Two baculoviruses were isolated and identified from Spodoptera litura; S. litura nucleopolyhedrovirus (SpltNPV) and S. litura granulovirus (SpltGV). The polyhedra of SpltNPV were about 0.9-1.83 µm in diameter containing multiple virions measuring about 100-280 nm wide and 320-410 nm long. The SpltNPV virions contained nucleocapsids (47-60 nm wide and 300-350 nm long) within an envelope, and the size of capsids measured about 58-60 nm wide and 300-330 nm long. The capsules of SpltGV were about 0.2-0.3 µm wide and 0.45-0.55 µm long containing single virion (60-73 nm wide and 245-267 nm long). The SpltGV nucleocapsids measured approximately 54-60 nm wide and 287-410 nm long, and found singly enclosed within an envelope. The SpltGV capsids measured about 36- 58 nm wide and 175-277 nm long. The restriction endonuclease analyses (REN) revealed that these two baculoviruses did not show any identical restriction pattern. The DNA size of the SpltNPV and the SpltGV was estimated to be 132 kb and 124 kb, respectively. The nucleotide sequence analysis of the polyhedrin gene of SpltNPV had 98% sequence identity to the known SpltNPV (accession number: AF037262); while the granulin gene of SpltGV had 81 % sequence identity to the granulin gene of Xestia c-nigrum granulovirus (accession number: U70069). Based on the sequence analysis, the SpltNPV and the SpltGV are placed as a taxon of Group II NPV and Group GV, respecti vely. Both viruses exhibited general symptoms of polyhedrosis and granulosis. The SpltNPV-infected larvae showed pinkish yellow at the dorsal and lateral sides, while the SpltGV-infected larvae exhibited whitish ventral. The SpltNPV caused a reduction in the larval size while the SpltGV-infected larvae increased in size with bloated integument when lower viral dosages were given. Both viruses infected fat bodies, Malphigian tubules, tracheal matrices, hypodermis, muscles and midguts. The SpltNPV replicated in the nucleus and spread the disease to susceptible tissues within 24-h postinoculation (pj). The SpltGV was found replicating in both nucleus and cytoplasm, and the disease spread gradually after 48-h pj. The LDso of both viruses in neonate larvae of S. litura were 9 .04xl02 polyhedra for SpltNPV and 1.26xl04 capsules for SpltGV. The LTso of both viruses were similar when neonate larvae were fed with similar ranges of viral dosages. The SpltNPV showed a higher virulence in S. litura larvae than the SpltGV. The characterization of these baculoviruses is of particular interest in view of its possible use in biological or integrated control.